A Study on the motifs of Sasak Songket weaving cloths in Lombok, Indonesia / Lalu Rizkyan Hakiky, Arba’iyah Ab. Aziz and Mohamad Kamal Abd. Aziz - Hakiky, Lalu Rizkyan; Ab. Aziz, Arba’iyah; Abd. Aziz, Mohamad Kamal (Faculty of Art and Design, 2023)
There are several types of weaving known on Lombok Island, one of which is songket weaving which is a type of weaving typical of the Sasak tribe. The problem of this research was the lack of literature that studies in depth the motifs and meaning of the symbols of the motifs on the Lombok woven cloth. The purpose of this study was to identify the motif and analyse the meaning of the symbols of the songket weaving motifs of Lombok, typical of the Sasak tribe. The research method used in this study is a qualitative approach and the data was analysed using Saussure’s semiotic theory. It was found that many types of songket woven motifs are dominated by flora and fauna motifs and celestial motifs, and the rest are geometric motifs. The meaning of symbols in the songket weaving motifs of Lombok is heavily influenced by local culture, Malay culture and also Islamic values. In addition, the environment and social life of the Sasak tribe, which used to be the majority of Hindus, also influenced the symbolism of the woven motifs. Further, it would be better to continue this study more thoroughly with a focus on the motifs, symbolism, and function of Lombok's woven fabrics and their relationship to the social and cultural aspects of the Sasak people on the island of Lombok, West Nusa Tenggara Province, Indonesia.